Human Resource Competence And Innovation Of Small And Medium Micro Enterprises (UMKM) Tangerang Regency - Suhara, Toni; Husin; Bangun, Cicilia Sriliasta (APTISI Transactions on Management (ATM), 2022)
This research looks at the influence of human resource competence and innovation on small and medium-sized micro-enterprises. The study uses a quantitative approach by testing hypotheses using statistics. Calculations are done based on statistical formulas with the help of the Smart PLS 2.0M3 application. The study uses a survey method, i.e., collects data from specific natural locations, but the researchers implement treatments in data collection by distributing tables, questions, structured tests, and interviews. The sample for the study was 65 respondents. The results of this study are: (1) The influence of market orientation on human resource competence has a positive and significant value. It is seen from the relationship between variables of 63,534 > 1.96. (2) There is a positive and significant influence between market orientation towards MSME innovation, it is seen from the relationship between variables 4,145 > 1.96. (3) There is a positive and significant influence between human resource competencies on MSME innovation. This is evident from the relationship results between variables 15,149 > 1.96. (4) There is a positive and significant influence between market orientation and human resource competence on MSME innovation. This is seen from the relationship results between variables of 78,683 > 1.96.